A multidisciplinary approach for the carved fenestration in floral design of malay vernacular architecture - Nursuriani Shaffee; Ismail Said (2011)
This paper presents an experimental study on complexity of pattern on Malay woodcarving in two samples of ventilation panel from two traditional old palaces in Kelantan and Terengganu. Existing methods of analytical review analysis for carved components rely extensively on interpretation analysis of measured drawing and none has been looking on scientific method as analysis technique. 2D image measured drawings of carving motifs were retrieved from the Centre for the Study of Built Environment in Malay World at Universiti Teknologi Malaysia as a pictorial data source. The data was analyzed using multidisciplinary point pattern analysis. Supported by historical study of carved fenestration, the result suggests that the background of building, status of the owner, the types of character design elements are influencing factors on complexity of pattern on carving pattern. The result implies that these methods are lead to new knowledge in this study, it also will allow architects and craftsmen to be more attentive in sustaining this authentic local architecture embellishment